Decoupled tricarboxylic acid cycle and glycolysis of Corynebacterium glutamicum combined with acetate supply promote high-yield biosynthesis of l-homoserine - Daobin Wang; Lu Xu; Junwen Yuan; Ruisi Wu; Xiyao Cheng; Jidong Liu; Ning Li (Synthetic and Systems Biotechnology)
l-Homoserine is a valuable intermediate with broad applications in the food, pharmaceutical, and chemical industries. Although Corynebacterium glutamicum has been engineered for the efficient biosynthesis of l-homoserine, both production efficiency and glucose conversion remain suboptimal. In this study, an engineered C. glutamicum strain capable of high-yield l-homoserine production from glucose was successfully developed. First, an engineered C. glutamicum strain capable of biosynthesizing l-homoserine using glucose as the sole carbon source was constructed with a yield of 0.38 g/g. To further enhance conversion efficiency, the expression of key genes in the tricarboxylic acid (TCA) cycle was repressed. Among the strategies evaluated, deletion of the aceE gene proved most effective in decoupling glycolysis from the TCA cycle, and acetate supplementation successfully restored cell growth in the decoupled strain. Subsequent metabolic rewiring, including modulation of acetylation efficiency, enhancement of the glyoxylate cycle, and promotion of fumarate-to-l-aspartate conversion, led to substantial l-homoserine accumulation. The engineered strain ultimately achieved an l-homoserine titer of 17.35 g/L with a yield of 0.56 g/g glucose, representing a 48 % increase. Finally, fed-batch fermentation was performed in a 5-L bioreactor using glucose and acetate as mixed carbon sources. The optimized strain, ACg23-6, produced 70.54 g/L l-homoserine within 96 h, with a yield of 0.58 g/g glucose and a productivity of 0.73 g/L/h, while consuming 80 g/L acetate. This decoupling strategy provided valuable insights for improving glucose conversion efficiency and acetate utilization in the microbial production of l-aspartate-derived compounds.